Impact of Fiscal Policies on Economic Growth and Poverty in Morocco: An analysis in Computable General Equilibrium - Nezha, Bousselhami; Moustapha, Hamzaoui (Archives of Business Research, 2018)
This work sets the objective of analyzing the impact that fiscal policies (fiscal and public expenditure) can have on economic growth and poverty in Morocco. This analysis is conducted through a computable general equilibrium model where the macro-micro link is established. The splitting of the household agent into a quintile makes the model a powerful instrument for analyzing the effects of these policies on the behavior of the different classes of households.